Answer:
b) 180 m, a) y = 3x
Step-by-step explanation:
1) Use constant acceleration equation:
x = x₀ + v₀ t + ½ at²
If we take down to be positive:
x = (0 m) + (0 m/s) (6 s) + ½ (9.8 m/s²) (6 s)²
x ≈ 180 m
2) The first distance covered is:
x = x₀ + v₀ t + ½ at²
x = (0) + (0) (10) + ½ a(10)²
x = 50a
The velocity it reaches after this is:
v = at + v₀
v = a(10) + (0)
v = 10a
The second distance covered is:
x = x₀ + v₀ t + ½ at²
y = x₀ + (10a) t + ½ at²
y = (0) + (10a) (10) + ½ a(10)²
y = 150a
Therefore:
y = 3x